On the Usefulness of Narratives: An Interdisciplinary Review and Theoretical Model. Issue 5 (5th March 2018) - Shaffer, Victoria A; Focella, Elizabeth S; Hathaway, Andrew; Scherer, Laura D; Zikmund-Fisher, Brian J
Abstract : The Narrative Immersion Model identifies parameters that predict the impact of narrative messaging through successive layers of engagement with the narrative: interest, identification, and immersion Abstract: Background: How can we use stories from other people to promote better health experiences, improve judgments about health, and increase the quality of medical decisions without introducing bias, systematically persuading the listeners to change their attitudes, or altering behaviors in nonoptimal ways? More practically, should narratives be used in health education, promotion, or behavior change interventions? Method: In this article, we address these questions by conducting a narrative review of a diverse body of literature on narratives from several disciplines to gain a better understanding about what narratives do, including their role in communication, engagement, recall, persuasion, and health behavior change. We also review broad theories about information processing and persuasion from psychology and more specific models about narrative messaging found in the health communication and marketing literatures to provide insight into the processes by which narratives have their effect on health behavior. Results: To address major gaps in our theoretical understanding about how narratives work and what effects they will have on health behavior, we propose the Narrative Immersion Model, whose goal is to identify the parameters that predict the specific impact of a particular narrative (e.g. persuade, inform, comfort, etc.) based on the type of narrative message (e.g. process, experience, or outcome narrative). Further, the Narrative Immersion Model describes the magnitude of the effect as increasing through successive layers of engagement with the narrative: interest, identification, and immersion. Finally, the Narrative Immersion Model identifies characteristics of the narrative intervention that encourage greater immersion within a given narrative. Conclusions: We believe there are important communication gaps in areas areas of behavioral medicine that could be addressed with narratives; however, more work is needed in order to employ narrative messaging systematically. The Narrative Immersion Model advances our theoretical understanding about narrative processing and its subsequent effects on knowledge, attitudes, and behavior.